Peningkatan Kerja Sama Antar Industri Kecil dan Menengah di Jawa Timur Dengan Pemanfaatan Aplikasi e-Collaborative Business - Lisana Lisana (Jurnal Informatika dan Sistem Informasi, 2015)
The Government, from year to year, always monitor and evaluate the empowerment of small to medium industries. Those industries are the backbone of the National Economic. Those small to medium industries have significant contribution to Gross Domestic Product (GDP), the main provider of job vacancy, and the source of the nation’s income through the export activities. One of the popular small to medium industries in East Java are the shoe manufacturing industries. The Ministry of Industry also has established a policy that the development of small to medium industries is done through the cluster approach. The problem faced by those industry clusters is the lack of collaboration among the cluster stakeholders that leads to insufficient synergy among them. This research aims to overcome those problems by developing the e-collaborative business application that could act as the solution to increase the effectiveness of the collaboration among those industry clusters.